Predictive factors for eating disorders in a cohort of Sicilian female students - Coniglio, Maria Anna; Commodari , Elena; Laganà, Pasqualina (Progress in Nutrition, 2020)
Identifying factors that contribute to the onset of eating disorders is fundamental to implement an early therapy. A total of 1025 female freshmen were screened to find predictive factors for eating disorders. The SCOFF Test, the EAT 26 and a questionnaire developed for the survey were used. In total, 10.5% of students showed a BMI